Development of Human Resources in Improving Teacher Competence at Madrasah Tsanawiyah Al-Fathimiyah Telukjambe Timur Karawang - Agustini, Putri Alfiani; Umar, Abubakar; Arifudin, Yadi Fahmi (Journal of Education Technology Information Social Sciences and Health, 2024)
This research will examine and describe the development of human resources in increasing teacher competence at MTs Al-Fathimiyah Telukjambe Timur Karawang. . The aims of this research are 1). To find out the development of human resources, 2). To find out the teacher's academic improvement, 3). To find out the supporting factors and inhibiting factors in improving teacher competence. This study used a qualitative description method where researchers directly examined the field and used data collection techniques in the form of observation, interviews and documentation which were conducted at MTs Al-Fathimiyah Telukjambe Timur Karawang. The results of this study reveal three findings, namely: 1). The development of human resources (HR) at MTs Al-Fathimiyah can be said to be quite good, but it is still being developed and improved, 2). In increasing teacher competence with an educator qualification program it is quite good, 3). There are factors supporting seriousness, earnest encouragement and a sense of responsibility by the principal towards teachers and inhibiting factors, namely in terms of the age of the teachers, some of whom have entered old age and the lack of principals in coordinating between the needs and obligations of teachers in carrying out class assignments. Conclusion Human Resource Development at MTs Al-Fathimiyah we always use coaching in the form of technical guidance both outside the school and inside the school and in improving teacher competence, namely with the current educational qualifications it has been implemented, even though the teaching ability of educators who already meet the qualifications is still limited.